CONTROL OF INTERCONNECTED ASYNCHRONOUS ELECTRIC DRIVE OF BRIDGE CRANE FOR MOVING BRIDGE WITHOUT INTERACTION OF WHEEL FLANGE WITH RAILS - Orlovsky, I. A.; But, Yu. S. (Radio Electronics, Computer Science, Control, 2024)
For multicriteria control of the interconnected multiimpellent electric drive of moving of the bridge crane, allowing to provide moving the crane without a contact with flanges of rails, the structure of a regulator of the general feedback is developed and analytical expressions for calculation of its parameters are received. Research of the developed system by a method of mathematical modelling is executed.